2011
DOI: 10.1371/journal.pcbi.1002121
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Signals from the T-Cell Receptor and the Interleukin-2 Receptor

Abstract: T cells orchestrate the adaptive immune response, making them targets for immunotherapy. Although immunosuppressive therapies prevent disease progression, they also leave patients susceptible to opportunistic infections. To identify novel drug targets, we established a logical model describing T-cell receptor (TCR) signaling. However, to have a model that is able to predict new therapeutic approaches, the current drug targets must be included. Therefore, as a next step we generated the interleukin-2 receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…The production of cytokines is essentially controlled by transcription factors [43]. In our study, transcription factors and related pathways were under-expressed in children with BPD.…”
Section: Discussionmentioning
confidence: 71%
“…The production of cytokines is essentially controlled by transcription factors [43]. In our study, transcription factors and related pathways were under-expressed in children with BPD.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, STAT3 has been confirmed as susceptibility gene for the disease (35) , and its activation is impaired in response to IL-10 in MS patients (36) , suggesting a defective response of regulatory Tr1 cells. Regarding the interactions that were decreased in MS patients compared to controls, PBMCs from patients with MS showed lowered inhibition of STAT5 by LCK suggesting impairment of the regulation of T/B-cell signaling and IL-2 trophic effects (37) or cytotoxicity (38) , as well as the regulation of the ubiquitination system modulated by CBL-B (39) . LCK is modulated by EVI5, and influences STAT5 in our analysis, both being susceptibility genes for MS (35) .…”
Section: Discussionmentioning
confidence: 99%
“…T-bet, which is also known to be crucial for long-term memory in CD8 + T cells (Intlekofer et al, 2005;Juedes, Glimcher, Szabo, von Herrath, & Sullivan, 2003) and maturation of NK cells (Townsend et al, 2004). More recently; STAT5, which has traditionally been associated with cytokine signalling and JAK kinases (Beyer et al, 2011), has now also been identified as a central regulator of naïve CD4 + T cell metabolism (Jones et al, 2019). Furthermore, although the GATA proteins have restricted expression patterns to some extent their functions can be interchangeable.…”
Section: Discussionmentioning
confidence: 99%